2007 Los que no fuimos - Grupo Teatro La Cochera (2017)
Actúan: Pablo Altamirano, marcelo asevedo, Walter Garabano, David Gerber, Nestor González, Hugo Olmos, Lalo Orellano, Hernán Rossi, Víctor Trapote | Asistencia artística: Graciela Mengarelli | Dirección: Paco Giménez | Consultado el 27 de julio de 2016 | http://www.alternativateatral.com/obra7682-los-que-no-fuimos